2020
DOI: 10.1038/s41388-020-01507-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of SUGP1 mimic mutant-SF3B1 splice pattern in lung adenocarcinoma and other cancers

Abstract: Genes involved in 3′-splice site recognition during mRNA splicing constitute an emerging class of oncogenes. SF3B1 is the most frequently mutated splicing factor in cancer, and SF3B1 mutants corrupt branchpoint recognition leading to usage of cryptic 3′-splice sites and subsequent aberrant junctions. For a comprehensive determination of alterations leading to this splicing pattern, we performed a pan-TCGA screening for SF3B1-specific aberrant acceptor usage. While the most of aberrant 3′-splice patterns were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…In untreated cells, we observed exon skipping (skipped exon, SE) as the most frequent event triggered by the mutations followed by alternative 3’ splice site (A3’SS) use; relatively few introns were impacted [using a difference percent splicing inclusion (ΔPSI) cut-off of ≥ |10%| and FDR > 0.01] (Figure 4E). Among these were changes in 3’ splice site usage in introns of the TMEM14C and ENOSF1 genes, which, strikingly, correspond exactly to changes observed previously in cells harboring SF3B1 cancer mutations or SUGP1 cancer mutations (Figure 4F, G, S4D-F) (Alsafadi et al, 2021; Liu et al, 2020).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In untreated cells, we observed exon skipping (skipped exon, SE) as the most frequent event triggered by the mutations followed by alternative 3’ splice site (A3’SS) use; relatively few introns were impacted [using a difference percent splicing inclusion (ΔPSI) cut-off of ≥ |10%| and FDR > 0.01] (Figure 4E). Among these were changes in 3’ splice site usage in introns of the TMEM14C and ENOSF1 genes, which, strikingly, correspond exactly to changes observed previously in cells harboring SF3B1 cancer mutations or SUGP1 cancer mutations (Figure 4F, G, S4D-F) (Alsafadi et al, 2021; Liu et al, 2020).…”
Section: Resultssupporting
confidence: 85%
“…SUGP1 has not yet been visualized in any spliceosome structure, nor are there orthologs in S. cerevisiae or S. pombe. Recent work has identified SUGP1 as a putative tumor suppressor: its loss from the spliceosome was suggested to underlie splicing and oncogenic phenotypes of SF3B1 tumor mutations, and mutations in SUGP1 found in tumors mimic the splicing phenotype of SF3B1 mutant tumors (Alsafadi et al, 2021; Liu et al, 2020; Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SUGP1 is an essential gene for coding splicing proteins [ 65 ]. Alsafadi et al [ 66 ] reported that SUGP1 loss and mutations induced abnormal splicing of SF3B1 (core subunit of spliceosome component) in lung adenocarcinoma. In the present study, increased CKM, MME, and MPO, and decreased ALDH1A2, CHGB, and SUGP1 might be related to energy metabolism, oxidative stress, proliferation or apoptosis, immune reaction and various adverse effects induced by ZEA.…”
Section: Discussionmentioning
confidence: 99%
“…NALM and K562), as well as non-blood transformed cell lines (e.g. HeLa and HEK293 cells) (Darman et al 2015; Alsafadi et al 2016; Mupo et al 2017; Hacken et al 2018; Paolella et al 2017; Saez et al 2017; Lee et al 2018; Yin et al 2019; Alsafadi et al 2021). In our study, we sought to determine the specific role of mutant SF3B1 itself and thus examined it in a non-blood/non-cancer cell type.…”
Section: Introductionmentioning
confidence: 99%